Genome Sequence Resource for Erysiphe necator NAFU1, a Grapevine Powdery Mildew Isolate Identified in Shaanxi Province of China (Retracted) - Xingyuan Zhang; Bo Mu; Kaicheng Cui; Min Liu; Guihua Ke; Yongtao Han; Ying Wu; Shunyuan Xiao; Ying-Qiang Wen (Molecular Plant-Microbe Interactions, 2021)
The authors of Zhang et al. 34:1446–1449 (2021) retracted this article because the initially reported genome assembly of NAFU1 was contaminated. This article was retracted on 28 November 2022, and the correction of the NAFU1 genome assembly at NCBI will be made in the future.Erysiphe necator is an economically important biotrophic fungal pathogen responsible for powdery mildew disease on grapevine. Currently, genome sequences are available for only a few E. necator isolates from the United States. Based on the combination of Nanopore and Illumina sequencing technologies, we present here the complete genome assembly for an isolate of E. necator, NAFU1, identified in China. We acquired a total of 15.93 Gb of raw reads. These reads were processed into a 61.12-Mb genome assembly containing 73 contigs with an N50 of 2.06 Mb and a maximum length of 6.05 Mb. Combining the results of three gene-prediction modules (i.e., an evidence-based gene modeler [EVidenceModeler], an ab initio gene modeler, and a homology-based gene modeler), we predicted 7,235 protein-coding genes in the assembled genome of E. necator NAFU1. This information will facilitate studies of genome evolution and pathogenicity mechanisms of E. necator and other powdery mildew species through comparative genome sequence analysis and other molecular genetic tools.[Graphic: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.